Tafsiran Transaksi Akun Game Online Serta Aspek Perlindungan Hukum Yang Terkena Scam dan Penipuan (BEDROG) - I Gusti Made Darwin Damareksa Putra; Dewa Gede Pradnya Yustiawan (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
This research is intended to examine and gain a deep understanding of the different types of legal protections applicable to online game account transactions affected by fraud and scams, both prior to and following the establishment of agreements, by referring to the current laws and regulations in Indonesia. The scope of this legal protection includes preventive measures as well as the reinstatement of consumer rights in transactions impacted by fraud or scams, within the framework of national law. The study aims to clarify the various forms of legal protection available to consumers and the legitimacy of online game account transactions according to Indonesian law. Furthermore, the research explores the processes involved in online game account transactions and the definitions and features of scams and fraud from both civil and criminal legal perspectives. It also integrates various pertinent laws, including the Consumer Protection Law, the Information and Electronic Transactions Law, the Civil Code (KUHPerdata), and the Criminal Code (KUHP), along with recent updates to the newly established Criminal Code.